Explanatory model of cognitive functioning in aging Multivariable model of neurocognitive functioning in aging - Pérez-Ramos, Ysela J. (2024)
Objective: To validate an explanatory model of cognitive functioning in older adults, based on inhibitory control, working memory and processing speed. Method: Explanatory-correlational design. 128 people between 60 and 85 years of age were evaluated with working memory and processing speed tests of the WAIS-IV intelligence scale, Stroop Test and Neuropsi. Results: Two models of structural equation analysis were applied. In model 1, with the total sample, inhibitory control better explains the cognitive functioning in adults aged 60 to 85 years (β=0.22; p<0.538). Model 2, which included age as a control variable, divided the sample into two age groups, and found that processing speed best predicted cognitive functioning in adults aged 60-70 years (β=2.329; p=0.030). but no variable predicted cognitive functioning in adults aged 71 to 85 years. The second model showed better fitting indices (CMIN/DF= 1.352; GFI = .950; CFI = .983 and RMSEA=.053). Conclusions: Inhibitory control and processing speed explain cognitive functioning during aging, but in different age groups, which validates the explanatory model that includes age as a control variable